National Health Interview Survey, 1991: Health Promotion and Disease Prevention Supplement ([Verlag nicht ermittelbar], 1993)
The purpose of the National Health Interview Survey (NHIS) is to obtain information about the amount and distribution of illness, its effects in terms of disability and chronic impairments, and the kinds of health services people receive. This supplement includes variables from the core Person File (see NATIONAL HEALTH INTERVIEW SURVEY, 1991 [ICPSR 6049]), including sex, age, race, marital status, veteran status, education, income, industry and occupation codes, and limits on activity. The variables unique to this supplement cover 12 topic areas that relate to the United States Department of Health and Human Services' "Healthy Year 2000" objectives: environmental health (radon, smoking in the home, and lead paint), tobacco (smoking history, use of tobacco, and health), nutrition (weight control and exercise), immunization and infectious disease (vaccinations and foreign travel), occupational safety and health (seat-belt use, smoking in the workplace, and wellness programs), heart disease and stroke (blood pressure and cholesterol concerns), other chronic and disabling conditions (diabetes, glaucoma, asthma, and mobility problems), clinical and preventive services (seat-belt usage and complete physical exam), physical activity and fitness (types and frequency of physical activity), alcohol (drinking history in past year), mental health (feelings of anger, depression, and boredom recently), and oral health (dental visits in past year).